2022
DOI: 10.1021/acsami.1c23086
|View full text |Cite
|
Sign up to set email alerts
|

Two-Dimensional Fillers Induced Superior Electrostatic Energy Storage Performance in Trilayered Architecture Nanocomposites

Abstract: Dielectric capacitors with ultrahigh power densities and fast charging/discharging rates are of vital relevance in advanced electronic markets. Nevertheless, a tradeoff always exists between breakdown strength and polarization, which are two essential elements determining the energy storage density. Herein, a novel trilayered architecture composite film, which combines outer layers of two-dimensional (2D) BNNS/poly(vinylidene fluoride-cohexafluoropropylene) (P(VDF-HFP)) with high breakdown strength and an inte… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
29
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8
1

Relationship

3
6

Authors

Journals

citations
Cited by 40 publications
(31 citation statements)
references
References 69 publications
0
29
0
Order By: Relevance
“…12,36,[51][52][53][54][55][56][57][58] The nanocomposite lm of P(VDF-HFP)/HAP@Al 2 O 3 NWs-4 exhibits the highest U N ($289%) among these classical nanocomposite lms. In addition, U d and E b of several composite lms with nanollers (including low dielectric constant, 15,25,59 high dielectric constant 15,[60][61][62][63][64][65] and core-shell structure 12,20,66 ) reported in the past are illustrated in Fig. 3d.…”
Section: Resultsmentioning
confidence: 98%
See 1 more Smart Citation
“…12,36,[51][52][53][54][55][56][57][58] The nanocomposite lm of P(VDF-HFP)/HAP@Al 2 O 3 NWs-4 exhibits the highest U N ($289%) among these classical nanocomposite lms. In addition, U d and E b of several composite lms with nanollers (including low dielectric constant, 15,25,59 high dielectric constant 15,[60][61][62][63][64][65] and core-shell structure 12,20,66 ) reported in the past are illustrated in Fig. 3d.…”
Section: Resultsmentioning
confidence: 98%
“…23,24 This is because the large-aspect-ratio 1D nanollers not only signicantly improve K, but also form an ordered dispersion center that could hinder the development of electrical trees to promote E b . [25][26][27] For example, Wang et al 28 revealed that 1D BT NFs loaded into a poly(vinylidene uoride) (PVDF) matrix exhibited larger K (11.03 vs. 14.69 at 1 kHz), better E b (300 vs. 370 MV m −1 ) and higher U d (4.86 vs. 8.78 J cm −3 ) than those of 0D BT NPs.…”
Section: Introductionmentioning
confidence: 99%
“…To further investigate the difference in conduction activation energy between pure PI and 5BN/PI-S nanocomposites, the activation energy ( A c ) could be fitted by the Arrhenius relation where σ­( T ), σ 0 , T , e , and K b represent the volume conductivity, prefactor, temperature, carrier charge, and Boltzmann constant, respectively. As illustrated in Figure a, the A c for PI and 5BN/PI-S nanocomposites is fitted by the volumetric conductivity measured at different temperatures.…”
Section: Resultsmentioning
confidence: 99%
“…10,28,34,35 For instance, more recently, it has been indicated that the introduction of 2D BNNs and MoS 2 into the PVDF-HFP matrix formed trilayered architecture composite films that could simultaneously improve polarization and breakdown strength, thus exhibit a prominent discharged energy density of 25.03 J cm −3 with a high efficiency of 77.4% at an electric field of 650 MV m −1 . 10…”
Section: Introductionmentioning
confidence: 99%